Introduction of antisense oligonucleotides into cells by permeabilization with streptolysin O - Barry, E L (BioTechniques, 1993)
Cellular uptake of antisense oligonucleotides is critical to their ability to inhibit gene expression. In the present study, phosphodiester oligodeoxynucleotides were introduced into cells during brief permeabilization with the pore-forming agent streptolysin O. The extent of antisense inhibition was dependent on the concentration of oligonucleotide present during permeabilization. In addition, the level of antisense inhibition was time-dependent; it reached a maximum at 18 h and subsequently diminished to control levels over the next 48 h. These results demonstrate the effectiveness of streptolysin O permeabilization as a means for simple and rapid introduction of oligonucleotides into eukaryotic cells